Congenital Absence of a Teat in a Japanese Black Heifer - Mohamed Elshabrawy Ghanem; Toshihiko Nakao; Chikako Yoshida (Case Reports in Veterinary Medicine)
A case of Japanese Black heifer with a congenital absence of teat (athelia) was observed at Highashi-Hiroshima Agricultural High School, Hiroshima Prefecture, Japan. The heifer was born after transfer of embryo from Japanese Black cattle. The sire of the heifer was a proven Japanese Black. The birth weight of the heifer was 27 kg. On physical examination of the heifer at 21 months after birth, the teat at fore left was absent and the remaining three teats were normal in shape without any physical abnormalities. Per rectal palpation of the genital organs revealed the normal cervix and uterine horns. It was difficult to palpate the ovaries due to the fat around the organs. Blood samples were taken for cytogenetic and DNA testing. The heifer had normal chromosomal set. The heifer was culled due to its mammary abnormality. This might be the first to report a case of congenital absence of a teat in Japanese Black heifers.